PROFIL FENOTIP DAN PRODUKSI PEJANTAN SAPI PERANAKAN ONGOLE DI WILAYAH SUMBER BIBIT KABUPATEN BOJONEGORO - Hariadi Darmawan; Bagus Purnama Irawan; Eko Marhaeniyanto; Karunia Setyowati Suroto (BUANA SAINS, 2025)
This study profiles the phenotypic characteristics and production performance of Peranakan Ongole (PO) bulls in Bojonegoro Regency, an officially designated PO cattle breed-source site, and evaluates their capacity to support sustainable community-based breeding. A descriptive-quantitative survey was conducted over two months in three subdistricts (Tambakrejo, Sekar, and Kedungadem), selecting 180 purposively sampled bulls aged ≤50 months. Primary data comprised qualitative (coat color, horn shape, ear hair pigmentation, and other SNI–specified traits) and quantitative (heart girth, body length, height at rump) phenotypic measurements; secondary data on birth, weaning, and one-year body weights were obtained via farmer questionnaires, key-informant interviews, and official records. Descriptive statistics revealed that all sampled bulls met SNI qualitative standards, with the sole exception of progressive ear-hair graying in mature animals. Quantitative traits consistently exceeded Class I SNI minimum (such as mean chest girth 163–191 cm; body length 130–158 cm; withers height 130–141 cm). Mean production weights were 20.0 ± 3.3 kg at birth, 116.5 ± 9.0 kg at weaning, and 138.3 ± 13.6 kg at one year, surpassing or matching earlier reports. Observed genotype, environment synergy, driven by abundant local forage and traditional management, underscores the bulls’ preserved genetic merit and breeding potential. These findings furnish a strategic basis for selective male choice and policy interventions to enhance PO genetic improvement and breeder livelihoods in Bojonegoro.